The role of customer satisfaction in mediating the influence of service quality and perceived value on brand loyalty - Devi, Anak Agung Diah Tarama; Yasa, Ni Nyoman Kerti (International research journal of management, IT and social sciences, 2021)
The study investigates how service quality and perceived value influence brand loyalty of Lion Air customers in Denpasar and how these relationships are mediated by customer satisfaction. The research was conducted in Denpasar, Bali. Sample size of 128 respondents was collected through a questionnaire and has been tested for its validity and reliability. The analysis technique used is Structural Equation Model (SEM) and using Smart PLS 3.0. The results showed that service quality, perceived value and customer satisfaction had a positive and significant effect on brand loyalty of Lion Air customers in Denpasar. Another result is that customer satisfaction is able to partially mediate the relationship between service quality and perceived value with brand loyalty of Lion Air customers in Denpasar. This research is expected to be empirical evidence for future research and be able to enrich the development of marketing management science related to service quality, perceived value, customer satisfaction and brand loyalty. The practical implication in this research is that Lion Air customer loyalty can be created when consumers feel that the quality of service provided by Lion Air meets their expectations, feels added value when using Lion Air, and feels right and satisfied when using Lion Air.